MOTIVASI PEKERJA OJEK KONVENSIONAL DALAM PERSAINGAN BISNIS TRANSPORTASI ONLINE (STUDI PADA JASA OJEK PANGKALAN DI KECAMATAN NGALIYAN KOTA SEMARANG) - Dian Triyani Triyani; Lulus Prapti; Aprih Santoso (Jurnal Dinamika Sosial Budaya, 2017)
Ojek is an informal public transport in Indonesia in the form of a motorcycle. Recently appeared a new breakthrough in terms of public transportation, which is an online motorcycle taxi that can be ordered through a smartphone. The conventional motorcycle taxi drivers who move to ojek online make conventional motorcycle taxi drivers complain. The formulation of this research problem is how conventional motorcycle taxi driver motivation in facing the business competition of transportation.This research was conducted at motorbike bases in Ngaliyan sub-district. Period of research implementation starting from October 2017. The focus will be investigated by researchers is the conventional motorcycle taxi drivers in the district Ngaliyan. Interviews were conducted on five conventional motorcycle taxi drivers.The results showed that the compensation factor, commitment, and work environment influence the motivation of conventional motorcycle taxi in maintaining their job and can face the competition of transportation business. The more acceptable compensation, high organizational commitment, and a good working the more motivated the worker will be to keep his job.